Features of translation Korean realia into Kazakh language - Тургaнбaй, A. К. (Journal of Oriental Studies, 2017)
This article is devoted to theoretical and practical analysis of translation problems in Kazakhstan through a review of the major difficulties in translating the realia from Korean into Kazakh language in a literary text. As you know, way of life, climatic factors, geographic location, history and society strongly influence the formation of some of the features of the culture and is displayed in the language of the nation. The importance of this work lies in the fact that today the problems of classification, characteristics and the translation of realia are still open.